Particle size of the 1601 CE Lake Lucerne tsunami event deposit - Valentin Nigg; Paola Bacigaluppi; David F Vetsch; Hendrik Vogel; Katrina Kremer; Flavio S Anselmetti (PANGAEA, 2021)
Results of particle size analysis of the siliciclastic fraction of an event deposit. Samples were taken from sediment core LU18-2 at depths ranging from 37.5 to 101.5 cm at 1 cm intervals. Grain size measurements were made using a Malvern Mastersizer 3000 particle size analyzer.
In: Nigg, V et al. (2021): Shallow-Water Tsunami Deposits: Evidence from Sediment Cores and Wave Propagation of the 1601 CE Lake Lucerne Event [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938716